Challenges to biobanking in LMICs during COVID-19: time to reconceptualise research ethics guidance for pandemics and public health emergencies?. Issue 7 (12th May 2021) - Singh, Shenuka; Cadigan, Rosemary Jean; Moodley, Keymanthri
Abstract : Biobanking can promote valuable health research that may lead to significant societal benefits. However, collecting, storing and sharing human samples and data for research purposes present numerous ethical challenges. These challenges are exacerbated when the biobanking efforts aim to facilitate research on public health emergencies and include the sharing of samples and data between low/middle-income countries (LMICs) and high-income countries (HICs). In this article, we explore ethical challenges for COVID-19 biobanking, offering examples from two past infectious disease outbreaks in LMICs where biobanking activities contributed to the perpetuation of global inequities. We focus on how the ethical imperative to promote the common good during public health emergencies can conflict with protecting the interests of biobank participants. We discuss how conducting biobank research under a waiver of informed consent during public health emergencies is ethically permissible, provided guidance is in place to prevent biopiracy and exploitation of vulnerable communities. We also highlight the need for biobank collaborations between LMICs and HICs to promote capacity building and benefit sharing. Finally, we offer guidance to promote the ethical oversight of biobanks and biobank research during the COVID-19 pandemic or other future public health emergencies.